Chest pain in the course of multiple myeloma - a clinical case study - Drab, Marcin; Szymczyk, Agnieszka; Tomczak, Waldemar; Drab-Urbanek, Elżbieta; Łapacz, Katarzyna; Hus, Marek; Podhorecka, Monika (Journal of Education, Health and Sport, 2018)
Introduction: Multiple myeloma (MM) is a rare blood cell proliferative disease characterized by the accumulation and proliferation of monoclonal plasmocytes. Clinical picture of MM includes bone pain, underlying osteolytic lesions, osteopenia or osteoporosis that often lead to pathological fractures. Aim: To draw attention to the unusual cause of chest pain and the holistic approach to analgesic therapy in patients with MM. Case report: A clinical case of a 66-year-old patient with chest pain intensified when moving and deep breathing was presented and cardiological and gastroenterological reasons were excluded. Initially, non-steroidal analgesics and weak opioids were used in the treatment with good effect, however, as time was passing the pain symptoms progressed. Diagnostic imaging was complemented by computed tomography which revealed massive destructive changes within the ribs with the presence of soft tissue masses infiltrating adjacent muscles. Based on additional tests, the patient was diagnosed with MM. Optimization of analgesic therapy has brought permanent pain relief and improved his quality of life. Summary: The modern approach to anelgesia in patients with MM includes not only the use of analgesics, but also radiotherapy, bisphosphonates/zoledronic acid, orthopaedic treatment and chemotherapy.